Color conversion film, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202611090162.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-20
AI Technical Summary
CN116635503A公开了一种改性乙烯醇系聚合物的制造方法,着眼于通过特定取代度的改性来改善聚乙烯醇的热塑加工性和耐水性,但同样未涉及色彩转换的应用场景,也未对该类材料的光学性能、与荧光粉的相容性等关键指标进行研究
(1)本发明完全摒弃了缩醛键结构,采用醚键和碳-碳键构成三维交联网络,从化学结构上彻底杜绝了醛类物质的产生。经Headspace GC-MS检测(检出限1 ppm),本发明色彩转换膜在120℃加热1小时后未检出丁醛,具有永久无醛特性。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of optoelectronic materials technology, specifically relating to a color conversion film, its preparation method, and its application. Background Technology
[0002] Color conversion films are key components in solid-state lighting for achieving white light or other colors, typically composed of organic resin binders and inorganic phosphors dispersed within them. Polyvinyl butyral (PVB) has been widely studied as an binder for this application due to its high transparency and excellent adhesion. However, the PVB molecular chain contains numerous acetal bonds, which undergo reversible breakage during high-temperature processing and use, continuously releasing aldehydes. This not only causes odor problems but, more seriously, chemically poisons the phosphor surface, leading to a continuous decline in light conversion efficiency.
[0003] Chinese patent CN115672064A discloses a method for preparing a polyvinyl alcohol nanofiltration membrane modified with grafted epoxy groups. This method involves grafting epoxy groups onto the polyvinyl alcohol molecular chain and then crosslinking it with a polyamine crosslinking agent to form a two-dimensional network structure. The crosslinking reaction can be completed without high temperature or strong acid catalysis, and the resulting membrane exhibits good stability and ultra-high flux. While this method utilizes epoxy groups to achieve crosslinking modification of polyvinyl alcohol, its application is limited to water treatment nanofiltration membranes, and it still uses polyamine crosslinking agents. The system contains small-molecule amines that can produce ammonia odor and pose a risk of aldehyde side reactions, which is fundamentally different from the purity and long-term optical stability requirements of optoelectronic applications. CN116635503A discloses a method for manufacturing modified vinyl alcohol polymers, focusing on improving the thermoplastic processability and water resistance of polyvinyl alcohol through modification with a specific degree of substitution. However, it also does not address color conversion applications, nor does it study key indicators such as the optical properties and compatibility with phosphors of this type of material.
[0004] It is particularly important to emphasize that the existing technology does not teach or imply that the application of epoxy crosslinked polyvinyl alcohol (PVA) systems to the field of color conversion membranes can be successful. On the contrary, due to the large number of hydroxyl groups in the PVA molecular chain, it is generally believed in the art that high hydroxyl content may lead to the following problems: (1) hydroxyl groups may undergo side reactions with the surface of some phosphors (especially nitride and oxynitride phosphors), reducing the quantum efficiency of the phosphors; (2) the strong polarity of hydroxyl groups leads to high viscosity of the coating solution, which is not conducive to the uniform dispersion of phosphors; (3) unmodified PVA membranes are brittle and lack flexibility due to excessively high hydrogen bond density. Therefore, when faced with the aldehyde release problem of PVB systems, those skilled in the art would not have the motivation to directly apply known epoxy crosslinked PVA nanofiltration membrane solutions to color conversion membranes, as this would introduce a series of new technical obstacles that do not exist or are not considered in the field of nanofiltration membranes. This invention achieves its goal by precisely controlling the glycidyl etherification degree of PVA within a specific range of 10-25 mol%. Extensive experimental screening revealed that when the degree of substitution falls within this range, the three technical obstacles mentioned above can be overcome simultaneously: (1) sufficient side-group shielding prevents the hydroxyl groups from poisoning the phosphor; (2) a moderate degree of substitution reduces the viscosity of the coating solution, facilitating uniform dispersion of the phosphor; and (3) moderate crosslinking and internal plasticizing effects within the side groups give the film both flexibility and strength, thus achieving a perfect balance between formaldehyde-free properties and overall performance. This critical range effect exceeds the scope expected by those skilled in the art based on conventional experiments, constituting a crucial basis for the inventiveness of this invention.
[0005] Therefore, there is an urgent need for a new type of conversion film matrix material that combines excellent comprehensive performance and formaldehyde-free properties in the field of optoelectronic applications. Summary of the Invention
[0006] The purpose of this invention is to provide a conversion film matrix material that fundamentally eliminates the generation of aldehydes, enabling the color conversion film to obtain a stable microenvironment that is permanently odorless and does not poison the phosphor.
[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a color conversion film, comprising the following steps: S1. Polyvinyl alcohol, catalyst, monoepoxy compound, and solvent are mixed and subjected to an etherification reaction to obtain a side-group modified polyvinyl alcohol solution; S2. Mix the light-converting pigment, the side-group modified polyvinyl alcohol solution, and the crosslinking agent evenly to obtain the coating liquid; S3. Apply the coating liquid to the substrate and heat to cure, thus obtaining the color conversion film.
[0008] Preferably, the mass ratio of polyvinyl alcohol, catalyst, and solvent in S1 is 100:(0.5-5):(500-2000); the amount of the monoepoxy compound is 10-40% of the molar amount of hydroxyl groups in the polyvinyl alcohol.
[0009] Furthermore, the degree of polymerization of polyvinyl alcohol in S1 is 500-2400, and the degree of alcoholysis is 88%-99%.
[0010] Preferably, the catalyst in S1 is at least one of boron trifluoride diethyl ether complex, p-toluenesulfonic acid, and sulfuric acid; more preferably, the catalyst is boron trifluoride diethyl ether complex.
[0011] Preferably, the monoepoxy compound in S1 is at least one of a monofunctional glycidyl ether containing a perfluoropolyether segment or a perfluoroalkyl segment, or a C2-C8 aliphatic monoglycidyl ether.
[0012] Preferably, the solvent in S1 is selected from at least one of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, or a mixture of the above with water.
[0013] Preferably, the solvent is a mixture of dimethyl sulfoxide and water, wherein the mass ratio of dimethyl sulfoxide to water is (70-90):(10-30).
[0014] Preferably, the etherification reaction in S1 is carried out at a temperature of 50-90°C for 4-12 hours.
[0015] Furthermore, after the etherification reaction in S1 is completed, the reaction product is precipitated in a precipitant, washed, and dried to obtain purified modified polyvinyl alcohol, which is then redissolved in a coating solvent.
[0016] Furthermore, the precipitant is at least one of deionized water or C1-C4 alcohol solvents; the coating solvent is selected from at least one of propylene glycol methyl ether acetate, butanone, ethyl acetate, and toluene.
[0017] Preferably, the mass ratio of the light-converting pigment, the side-group modified polyvinyl alcohol solution, and the crosslinking agent in S2 is (20-100):100:(1-5).
[0018] Preferably, the light-converting pigment in S2 is at least one of cerium-doped yttrium aluminum garnet, nitride red phosphor, oxynitride green phosphor, or quantum dot.
[0019] Preferably, the crosslinking agent is a compound containing at least two epoxy groups, selected from at least one of trimethylolpropane triglycidyl ether, bisphenol A diglycidyl ether, and polyethylene glycol diglycidyl ether.
[0020] Preferably, a curing accelerator is also added to step S2, wherein the curing accelerator is an imidazole compound or a tertiary amine compound; preferably, the curing accelerator is 2-methylimidazole.
[0021] Preferably, the solid content of the coating liquid in S2 is 10-40 wt%.
[0022] Preferably, the heating and curing temperature in step S3 is 80-130℃, and the curing time is 0.5-4 hours.
[0023] The present invention also provides a color conversion film, which is prepared by the above-described preparation method.
[0024] Preferably, the color conversion film is characterized by having a glycidyl etherification degree of 10-25 mol in the polyvinyl alcohol backbone.
[0025] The present invention also provides a light-emitting device, including a light-emitting element and the aforementioned color conversion film disposed on the light output path of the light-emitting element; the light-emitting element is an LED or an OLED.
[0026] It contains at least the following beneficial technical effects: (1) This invention completely eliminates the acetal bond structure and uses ether bonds and carbon-carbon bonds to form a three-dimensional cross-linked network, thus completely eliminating the generation of aldehydes from a chemical structure perspective. According to Headspace GC-MS detection (detection limit 1 ppm), the color conversion film of this invention did not show any butyraldehyde after heating at 120°C for 1 hour, and has permanent aldehyde-free properties.
[0027] (2) The color conversion film of the present invention has a light flux retention rate of >93% after aging at 85℃ / 85%RH for 1000 hours, which is significantly better than the traditional PVB system and organosilicon system, and its service life is greatly extended.
[0028] (3) By precisely controlling the degree of glycidyl etherification substitution within the critical range of 10-25 mol%, this invention simultaneously overcomes the technical obstacles of poor phosphor compatibility, high viscosity of coating liquid and high film brittleness caused by excessive hydroxyl groups in the PVA system, and achieves a good balance between adhesion and flexibility.
[0029] (4) The preparation process of this invention is mild and environmentally friendly, and the coating liquid has a long service life. It is suitable for roll-to-roll continuous coating production and has good industrial feasibility. Detailed Implementation
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0032] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0033] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.
[0034] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0035] Unless otherwise specified, "room temperature" and "normal temperature" in this invention refer to 25±2℃.
[0036] Unless otherwise specified, all raw materials or instruments used in the following embodiments of the present invention are commercially available.
[0037] Example 1 I. Etherification Modification of PVA In a reactor equipped with stirring and nitrogen protection, 100 parts of PVA with a degree of polymerization of 1000 and a degree of hydrolysis of 99% were dissolved in a mixed solvent of dimethyl sulfoxide (DMSO) and deionized water (mass ratio 90:10). The mass concentration of the PVA solution was approximately 10 wt%, i.e., approximately 810 parts of DMSO and approximately 90 parts of deionized water were used. The mixture was heated to 80°C to dissolve the PVA. The temperature was then lowered to 50°C, and 2 parts of boron trifluoride diethyl ether complex were added as a catalyst. Under stirring, a mixture of 30 parts of butyl glycidyl ether and 20 parts of perfluorooctyl ethyl glycidyl ether was slowly added dropwise, and the mixture was heated to 70°C and reacted for 8 hours. After the reaction was complete, the viscous solution was added dropwise to a large amount of deionized water to precipitate the PVA. The precipitate was filtered, repeatedly washed with deionized water until the washings were neutral to thoroughly remove the catalyst and unreacted substances, and then dried to obtain a modified PVA resin with a glycidyl etherification degree of approximately 15 mol%. The degree of glycidyl etherification substitution was determined by ¹H NMR: the modified PVA resin was dissolved in deuterated DMSO, and the samples were collected using a 400MHz NMR spectrometer. 1 H-spectroscopy. Using the methylene proton signal (δ 3.8-4.0 ppm) of the PVA main chain as an internal standard, the integral area ratio of the methylene proton signal (δ 3.2-3.5 ppm) in the glycidyl ether side group to the methylene proton of the main chain was calculated, and the degree of glycidyl etherification substitution was obtained.
[0038] In this step, partially replacing DMSO with water significantly reduces solvent costs. The introduced deionized water does not affect the etherification reaction between the PVA side hydroxyl groups and glycidyl ether. The mass ratio of DMSO to water can be flexibly adjusted within a wide range from 90:10 to 70:30 to achieve a balance between solvent costs and product performance. When the water ratio is high (e.g., 70:30), it is recommended to appropriately extend the reaction time and / or increase the amount of catalyst to ensure that the degree of substitution reaches the target range. The structure and properties of the obtained product are not substantially different from those obtained using pure DMSO solvent.
[0039] II. Preparation of Coating Solution and Film Formation Take the modified PVA solution prepared according to the above steps, with a modified resin solid content of approximately 50 parts, and dissolve it in 250 parts of propylene glycol methyl ether acetate. Add 30 parts of YAG:Ce yellow phosphor and disperse it in a high-speed homogenizer at 8000 rpm for 10 minutes to obtain a uniform dispersion. Before coating, add 1.5 parts of trimethylolpropane triglycidyl ether as a crosslinking agent and 0.5 parts of 2-methylimidazole as a curing accelerator, and stir to remove bubbles. Apply the coating solution to a PET release film, cure at 100℃ for 1 hour, and then cure at 120℃ for 30 minutes to obtain a color conversion film with a thickness of approximately 70 μm.
[0040] The butyraldehyde release from the obtained conversion membrane was detected using the following method: The sample was placed in a 20 mL headspace vial and heated to equilibrate at 120 °C for 1 hour. An Agilent 7890A-5975C gas chromatograph-mass spectrometer equipped with a DB-624 capillary column (30 m × 0.25 mm × 1.4 μm) was used. The headspace sampler was heated to 120 °C, the injection time was 1 min, and the column temperature was maintained at 40 °C for 5 min, then increased to 250 °C at a rate of 10 °C / min and maintained for 2 min. Mass spectrometry was performed in selected ion mode to detect the characteristic ions of butyraldehyde at m / z 44 and 72. The results showed that butyraldehyde was not detected (detection limit 1 ppm).
[0041] Example 2 To determine the optimal range of glycidyl etherification degree of substitution, comparative experiments were conducted with different degrees of substitution (the amount of crosslinking agent was fixed at 3 parts / 100 parts of resin, and the amount of modified resin for each degree of substitution was evaluated by parallel coating with 100 parts as the baseline): Table 1 The results show that an optimal balance between adhesive strength, flexibility, and optical stability can be achieved within the substitution range of 10-25 mol%. Below 10 mol%, insufficient hydroxyl group blocking leads to significant film brittleness (the minimum radius of curvature of pure PVA is only 1 mm); above 25 mol%, excessive blocking of side hydroxyl groups results in a significant decrease in adhesive strength (peel strength drops below 14 N / 25 mm), and the crosslinking network becomes too loose due to the reduction in crosslinkable sites, leading to deterioration in aging performance (light flux retention rate drops below 91% after 1000 h). The 10-25 mol% range exhibits a clear performance critical point effect, meaning that all properties meet practical requirements within this range, while at least one key performance characteristic deteriorates significantly once this range is exceeded. This critical point effect was confirmed only after extensive experimental screening and cannot be expected by those skilled in the art through routine experiments.
[0042] Comparative Example 1 Using the method described in Example 1 of Japanese Patent Application Publication No. 2008-250119, low-residual-aldehyde PVB particles (total content of butyraldehyde and 2-ethyl-2-hexenal <50ppm, i.e., free aldehydes are reduced to a low level through enhanced water washing / stripping, but the acetal bond structure on the PVB molecular chain itself is not changed) were prepared. The PVB was dissolved in the same solvent, and an equal mass of YAG:Ce phosphor and an equivalent amount of isocyanate crosslinking agent (Desmodur N3300) were added. The mixture was cured at 130°C to obtain a PVB color conversion film of equal thickness.
[0043] Comparative Example 2 The resin of this invention was replaced with a commercially available two-component silicone encapsulant (Dow Corning OE-6550), and an equal mass of YAG:Ce phosphor was encapsulated between two PET films according to the manufacturer's recommended process. The film was then cured at 120°C to obtain a silicone-based color conversion film.
[0044] Table 2 Comprehensive Performance Evaluation Results analysis: Formaldehyde-free characteristics: Although the PVB raw material in Comparative Example 1 had its residual free aldehyde reduced to <50 ppm through a water washing / stripping process (an improvement direction of Japanese Patent Application Publication No. 2008-250119), the intrinsic reversible breaking of acetal bonds on the PVB molecular chain was not addressed. Therefore, after heating at 120°C for 1 hour, 28 ppm of butyraldehyde release was still detected—this release amount far exceeds the residual aldehyde level of the raw material, proving that acetal bonds continued to break during heating to generate new butyraldehyde. In contrast, Example 1 used an etherified crosslinking structure without acetal bonds. Under the same conditions, no butyraldehyde release was detected above the detection limit (<1 ppm), fundamentally verifying the effectiveness of the acetal-free structure design: This invention does not rely solely on process improvements to "reduce residual aldehydes," but rather completely avoids the acetal bond as an aldehyde source at the chemical bond level.
[0045] Optical stability: In a clean chemical environment, Example 1 still maintained a luminous flux retention rate of up to 93% after 1000 hours of aging, far exceeding the PVB system (62%) and also superior to the organosilicon system (88%), fully demonstrating the key role of the formaldehyde-free microenvironment in extending the phosphor's lifetime.
[0046] Adhesion: The etherified PVA system of Example 1 maintains good adhesion to both glass and PET, which is significantly better than that of silicone and close to that of traditional PVB.
[0047] Flexibility: The moderately cross-linked Example 1 has acceptable flexibility (minimum radius of curvature 3 mm), which is close to that of the PVB film (2 mm).
[0048] The preparation method of this invention can be extended to roll-to-roll continuous coating processes. Modified PVA resin can be synthesized in batches; the feed amount based on 100 parts PVA can be easily scaled up to hundreds of kilograms without fundamentally adjusting the reaction conditions, resulting in a robust process. After preparation, the coating solution is continuously coated onto PET substrates using slot coating or microgravure coating, followed by multi-stage oven curing at a speed of 2-5 m / min. The pot life of the coating solution can be extended to over 12 hours by reducing the amount of curing accelerator or selecting a latent accelerator (such as a thermally decomposable amine accelerator), meeting the needs of continuous industrial production.
[0049] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a color conversion film, characterized in that, Includes the following steps: S1. Polyvinyl alcohol, catalyst, monoepoxy compound, and solvent are mixed and subjected to an etherification reaction to obtain a side-group modified polyvinyl alcohol solution; S2. Mix the light-converting pigment, the side-group modified polyvinyl alcohol solution, and the crosslinking agent evenly to obtain the coating liquid; S3. Apply the coating liquid to the substrate and heat to cure, thus obtaining the color conversion film.
2. The preparation method according to claim 1, characterized in that, The mass ratio of polyvinyl alcohol, catalyst, and solvent in S1 is 100:(0.5-5):(500-2000); the amount of monoepoxy compound used is 10-40% of the molar amount of hydroxyl groups in the polyvinyl alcohol.
3. The preparation method according to claim 2, characterized in that, The catalyst in S1 is at least one of boron trifluoride diethyl ether complex, p-toluenesulfonic acid, and sulfuric acid.
4. The preparation method according to claim 2, characterized in that, The monoepoxy compound in S1 is at least one of a monofunctional glycidyl ether containing a perfluoropolyether segment or a perfluoroalkyl segment, or a C2-C8 aliphatic monoglycidyl ether.
5. The preparation method according to claim 1, characterized in that, The mass ratio of light-converting pigment, side-group modified polyvinyl alcohol, and crosslinking agent in S2 is (20-100):100:(1-5).
6. The preparation method according to claim 1, characterized in that, The light-converting pigment in S2 is at least one of cerium-doped yttrium aluminum garnet, nitride red phosphor, oxynitride green phosphor, or quantum dot.
7. The preparation method according to claim 5, characterized in that, The crosslinking agent is a compound containing at least two epoxy groups, selected from at least one of trimethylolpropane triglycidyl ether, bisphenol A diglycidyl ether, and polyethylene glycol diglycidyl ether.
8. A color conversion film, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
9. The color conversion film according to claim 8, characterized in that, The glycidyl etherification degree of the polyvinyl alcohol backbone in the color conversion film is 10-25 mol.
10. A light-emitting device, characterized in that, It includes a light-emitting element and a color conversion film as described in claim 8 disposed on the light output path of the light-emitting element; the light-emitting element is an LED or an OLED.
Citation Information
Patent Citations
Grafted epoxy group modified polyvinyl alcohol nanofiltration membrane and preparation method thereof
CN115672064A
Modified vinyl alcohol polymer, method for producing modified vinyl alcohol polymer, particles, aqueous solution, coating liquid, coated article, molded article, release
CN116635503A
Binder for heat developable photosensitive material
JP2008250119A